Edukasi Penggunaan Obat Pada Kehamilan dan Menyusui Di Banjar Wongaya Kaja Desa Wongaya Gede - Pande Made Desy Ratnasari; Nila Yuliawati, Agustina; lestari, Gusti; Rama Wijaya Putra, I Wayan (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
The use of medication during pregnancy and breastfeeding to treat the various complaints experienced requires special attention. Lack of knowledge regarding drug use can cause serious side effects on the fetus and breastfeeding children. To prevent this, education is provided regarding the safe use of drugs during pregnancy and breastfeeding. The method used is providing counseling using power point tools and leaflets. The target respondents were women in  Wongaya Kaja, Wongaya Gede Village. The frequency of correct answers is presented to make it easier to see the respondent's level of knowledge before and after counseling. Next, the respondent's level of knowledge was analyzed using the Wilcoxon statistical (95% confidence level) to see whether any changes had occurred. The conclusion of this program is that there was a significant increase in respondents' knowledge (p value=0.008) before and after providing the information by 16.5%.